Manajemen Kepala Sekolah Dalam Pembinaan Prestasi di SMA Negeri 1 Gerung Lombok Barat - Haerul Anam; Yayan Gustiran (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2023)
As a manager, the principal has a decisive role in school management, the success or failure of the school's goals can be influenced by how the principal carries out management functions. The management functions are planning, organizing, implementing, and supervising. In this case, it is very important to do so in order to realize the determined goals effectively and efficiently. This study uses a qualitative approach. Data collection procedures were carried out through interviews, observation and documentation. The research lasted for almost six months involving the Principal, Deputy Head of Curriculum, Deputy Head of Student Affairs and senior teachers. Analysis of the data using the concept of analysis by Miles and Huberman (1984). Checking data validity through credibility test, transferability test, dependability test and confirmability test. The results showed that managerial development of student achievement at SMAN 1 Gerung was carried out in several stages according to the management function, namely planning, organizing, implementing and evaluating. The obstacle in fostering student achievement is that students do not understand the material and intentions not from themselves (Invitation to Friends). And the solution is that teachers must be good at delivering material, believe in their own abilities, solidify the team, create different programs, approach parents, establish effective communication, complete infrastructure, instill values ??of struggle, and hold meetings. The impact of Achievement Development on Student Achievement is derived from internal factors such as team solidarity, enthusiasm, high performance and sincerity. While external such as parental solidarity, networking and infrastructure. Keywords: Strategic Management, Principal Management, Achievement Development Sebagai manajer, kepala sekolah memiliki peran yang menentukan dalam pengelolaan sekolah, berhasil tidaknya tujuan sekolah dapat dipengaruhi bagaimana kepala sekolah menjalankan fungsi-fungsi manajemen. Fungsi-fungsi manajemen tersebut adalah perencanaan, pengorganisasian, pelaksanaan, dan pengawasan. Dalam hal ini sangat penting untuk dilakukan demi terwujudnya tujuan yang ditentukan secara efektif dan efisien. Penelitian ini menggunakan pendekatan  kualitatif. Prosedur pengumpulan data dilakukan melalui wawancara, observasi dan dokumentasi. Penelitian berlangsung selama hampir enam bulan dengan melibatkan Kepala Sekolah, Waka Kurikulum, Waka Kesiswaan dan  guru senior. Analisis data menggunakan konsep analisis oleh Miles dan Huberman  (1984). Pengecekan keabsahan data melalui uji kredibilitas, pengujian transferability, pengujian dependability dan pengujian confirmability. Hasil penelitian  bahwa manajerial  pembinaan prestasi Siswa di SMAN 1 Gerung dilakukan dengan beberapa tahap sesuai fungsi manajemen, yaitu perencanaan, pengorganisasian, pelaksanaan dan valuasi.  Kendala dalam pembinaan prestasi siswa adalah siswa kurang memahami materi dan niat bukan dari diri sendiri (Ajakan Teman). Dan solusinya adalah guru harus pandai menyampaikan materi, percaya dengan kemampuan sendiri, mempersolid Tim, membuat Program yang berbeda, melakukan pendekatan dengan orang tua, menjalin Komunikasi yang efektif, melengkapi Sarana Prasarana, menanamkan Nilai perjuangan, Mengadakan Rapat. Dampak Pembinaan Prestasi terhadap Prestasi Siswa adalah berasal dari faktor internal seperti solidaritas tim,semangat, kinerja tinggi dan ikhlas. Sedangkan  eksternal seperti solidaritas wali murid, networking dan sarana prasarana. Kata kunci: Manajemen Strategik, Manajemen Kepala Sekolah, Pembinaan Prestasi